Pengelolaan Sumber Daya Manusia Di Perusahaan Percetakan CV. Harapan Baru - Kusuma, Garcia Luciano, Ahmad Mardalis ,SE., M.B.A (2017)
The purpose of this study was to determine how to manage human resources in terms of manpower procurement, development, compensation, integration, maintenance, termination of employment so that could be a source of competitive advantage for CV. Harapan Baru. The population in this study were all employees of CV, Harapan Baru and samples used in this study is the manager of the company and head of the division, the head of the human resources department and others who support this research. The purpose of this study was to determine how to manage human resources in terms of manpower procurement, development, compensation, integration, maintenance, termination of employment so that could be a source of competitive advantage for CV. Harapan Baru. The population in this study were all employees of CV, Harapan Baru and samples used in this study is the manager of the company and head of the division, the head of the human resources department and others who support this research. The results of this research note that human resource management is part of the general management that focuses on human resources. To manifest certain results through people. This means that human resources is important and dominant role in management. The function of human resource management consists of human resource management as a managerial function Planning , Organizing , Directing , Controlling , as well as human resources management as the operational functions (Procurement of Labor or the Procurement Human Resources (recruitment), Development , Compensation , Integration , Maintenance , Termination of Employment . Therefore management in any activity undertaken by a person or a human being as an actor or actors is needed for each job or organization can run well.